2006
DOI: 10.1002/sia.2218
|View full text |Cite
|
Sign up to set email alerts
|

The initial oxidation of zirconium—oxide‐film microstructure and growth mechanism

Abstract: The initial stage of thermal oxidation of bare Zr within the temperature range of 373-773 K at a pO 2 of 2 × 10 −6 Pa was investigated by combined application of angle-resolved XPS (AR-XPS) and in situ spectroscopic ellipsometry (SE). A model description of the oxide-film growth kinetics was achieved adopting coupled currents of cations and electrons within a surface-charge field. The model could be fitted very well to the experimental data, thereby yielding profound knowledge of the relation between the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 8 publications
6
23
0
Order By: Relevance
“…5 b, e) reach a limiting value of ~0.7-0.9 nm. Similar self-limiting thicknesses have been obtained for the natural oxidation of Zr both from MD and experiments [25,27,55]. In addition, Mathieu et al [56] reported natural oxide film thicknesses ranging from 0.…”
Section: Case Study: Oxidation Of Ta (110) Surfacesupporting
confidence: 72%
“…5 b, e) reach a limiting value of ~0.7-0.9 nm. Similar self-limiting thicknesses have been obtained for the natural oxidation of Zr both from MD and experiments [25,27,55]. In addition, Mathieu et al [56] reported natural oxide film thicknesses ranging from 0.…”
Section: Case Study: Oxidation Of Ta (110) Surfacesupporting
confidence: 72%
“…Another peak for the oxygen atoms below the sample surface lies at 531.4 eV. In previous studies [25], this was attributed to ZrO X . However, the same binding energy is characteristic for Zr(OH) 4 as well and the possibility that this phase is present in the oxide layers cannot be disproven [23].…”
Section: Oxidationmentioning
confidence: 92%
“…They correspond to oxide material having gradients of Zr-enrichment and O-deficiency. This suggests that the defect structure in this part consists of both oxygen vacancies and Zr interstitials [24,25]. The last spectra collected at the deepest point in the sample, corresponds to elemental Zr.…”
Section: Oxidationmentioning
confidence: 98%
“…ers for the outward "hopping" of cations into and through interstices of the oxygen ion arrangement of the developing oxide film and is given by E = V k / L, where V k represents the established potential and L represents the thickness of the oxide film. Based on the low-temperature oxidation studies of aluminum by Jeurgens et al, 50,51 it is possible to get an estimate of the established kinetic potential ͑V k ϳ 2 V͒. Additionally, in case of field-assisted oxidation, there is an externally applied electric field of 10 MV/cm.…”
Section: E Calculation Of Activation Energymentioning
confidence: 99%